2010
DOI: 10.1002/anie.201003328
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Framework Materials: Theoretical Predictions and Experimental Results

Abstract: A promising storage medium for hydrogen and other gases is a graphene oxide framework (GOF) that consists of layers of GO connected by benzene‐1,4‐diboronic acid (B14DBA) pillars (see picture). Theoretical predictions and the initial experimental results are presented for this cheap and environmentally friendly building block for nanoporous materials with better gas adsorption properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
275
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(301 citation statements)
references
References 14 publications
20
275
1
1
Order By: Relevance
“…Despite this history, the structure of GO is still under debate. GO based materials have generated incredible interest for energy-related applications because of its multifunctional flexibility [25,26]. Moreover, GO has recently been studied for various biological applications [27], and has been applied in areas such as fabrication of intercalated GO composites [28].…”
Section: Simulation Details and Methodsmentioning
confidence: 99%
“…Despite this history, the structure of GO is still under debate. GO based materials have generated incredible interest for energy-related applications because of its multifunctional flexibility [25,26]. Moreover, GO has recently been studied for various biological applications [27], and has been applied in areas such as fabrication of intercalated GO composites [28].…”
Section: Simulation Details and Methodsmentioning
confidence: 99%
“…Calculations have shown that a GO framework (GOF) which can be prepared from GO and benzenediboronic acid could be used for hydrogen adsorption (Fig. 13b), 170,171 predicting that the GOF can theoretically achieve 6.1 wt% H 2 uptake at 77 K and 1 bar. However, the experimental studies only showed a maximum uptake of 1 wt %.…”
Section: Gas Adsorptionmentioning
confidence: 99%
“…However, the experimental studies only showed a maximum uptake of 1 wt %. 170 In a similar study Srinivas et al used solvothermal reactions to prepare a porous GOF. 172 The obtained framework pillared by 1,4-phenyldiboronic acid had a maximum adsorption capacity of 1.2 wt% at 77 K and 10 bar.…”
Section: Gas Adsorptionmentioning
confidence: 99%
“…Therefore, the charge and discharge kinetics must be very high. Recently, it was reported that by using of different activation procedures other than heat treatment, such as chemical reduction, to remove unreacted functional groups the O/C ratio could be reduced and improve the surface area and adsorption capacity of graphene oxide frameworks (GOFs) increases significantly [61]. Moreover, doping effect also can increase the capacity of hydrogen storage in graphene: the maximum hydrogen storage capacity in lithium ion doped pillared graphene material (Fig.15) around 7.6 wt% in the condition of 77 K and 100 bar pressure [10].…”
Section: Graphene and Graphanementioning
confidence: 99%